Evaluasi daya dukung lahan permukiman rawan bencana gempabumi Panjangrejo, Pundong, Bantul, DIY - Putri, Fairus Jelita Regita; Prasetya, Johan Danu; Santoso, Dian Hudawan (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2022)
The Pundong District was the epicenter of a magnitude 6.3 SR earthquake with a shallow depth of around 10 kilometers that occurred in 2006. According to statistics on tectonic earthquake casualties in the Pundong sub-district, 152 people were killed in the village of Panjangrejo, 696 people were badly injured, and 1,220 people sustained minor injuries. There were a total of 2,704 homes destroyed, and 2,293 were severely damaged. The aim of the research was to assess the carrying capacity of the land in earthquake-prone populated areas. If residential property is developed in excess of the land's carrying capacity, it will have a negative influence on environmental quality and may even cause natural disasters. Multiple physical data were combined using the overlay technique. On the basis of the categorization of the level land carrying for settlement area, the results indicate that the carrying capacity for settlement area in the earthquake affected Panjangrejo Village, Pundong District, Bantul Regency falls into two classes: appropriate and less suitable. Class I (appropriate) residential land is 2,897,050 m2 with a 54% carrying capacity, whereas class II (less suitable) residential land is 2,498,076 m2 with a 46% carrying capacity.